Pengaruh Media Video pada Kelas Ibu Hamil terhadap Pengetahuan Sikap dan Perilaku Pemilihan Penolong Persalinan - Kirana Candra Sari (Journal for Quality in Women's Health, 2019)
Maternal mortality during labor is very closely related to less skilled helpers and inadequate tools. Therefore labor should be assisted by skilled health workers because paraji is not equipped with emergency handling skills. The use of videos in pregnant classes can increase the knowledge, attitudes and behaviors of mothers to deliver to health workers. The purpose of this study was to determine the effect of video media on the class of pregnant women on knowledge, attitudes and behaviors of delivery helper selection.The design of this study used quasi-experimental with a randomized subjects post test only control group design approach. The researcher used the random assignment sampling method. This research was conducted in November 2018 in the Padasuka Community Health Center area, Bandung City, Bandung City Health Office.